International Survey of Critically Ill Children With Acute Neurologic Insults: The Prevalence of Acute Critical Neurological Disease in Children. Issue 4 (April 2017) - Fink, Ericka L.; Kochanek, Patrick M.; Tasker, Robert C.; Beca, John; Bell, Michael J.; Clark, Robert S. B.; Hutchison, Jamie; Vavilala, Monica S.; Fabio, Anthony; Angus, Derek C.; Watson, R. Scott
Abstract : Objective: The international scope of critical neurologic insults in children is unknown. Our objective was to assess the prevalence and outcomes of children admitted to PICUs with acute neurologic insults. Design: Prospective study. Setting: Multicenter ( n = 107 PICUs) and multinational (23 countries, 79% in North America and Europe). Patients: Children 7 days to 17 years old admitted to the ICU with new traumatic brain injury, stroke, cardiac arrest, CNS infection or inflammation, status epilepticus, spinal cord injury, hydrocephalus, or brain mass. Interventions: None. Measurements and Main Results: We evaluated the prevalence and outcomes of children with predetermined acute neurologic insults. Child and center characteristics were recorded. Unfavorable outcome was defined as change in pre-post insult Pediatric Cerebral Performance Category score greater than or equal to 2 or death at hospital discharge or 3 months, whichever came first. Screening data yielded overall prevalence of 16.2%. Of 924 children with acute neurologic insults, cardiac arrest (23%) and traumatic brain injury (19%) were the most common. All-cause mortality at hospital discharge was 12%. Cardiac arrest subjects had highest mortality (24%), and traumatic brain injury subjects had the most unfavorable outcomes (49%). The most common neurologic insult was infection/inflammation in South America, Asia, and the single African site but cardiac arrest in the remaining regions. Conclusions: Neurologic insults are a significant pediatric international health issue. They are frequent and contribute substantial morbidity and mortality. These data suggest a need for an increased focus on acute critical neurologic diseases in infants and children including additional research, enhanced availability of clinical resources, and the development of new therapies. Abstract : Supplemental Digital Content is available in the text.